ANALYSIS OF KALECIK KARASI GRAPE PRODUCER'S APPROACHES TO AGRICULTURAL INSURANCE: EXAMPLE OF KALECIK DISTRICT OF ANKARA PROVINCE (Third Sector Social Economic Review, 2021)
In this study, the approaches of Kalecik Karası grape producers in Kalecik district of Ankara province towards agricultural insurance have been determined. Kalecik Black grape producers in 11 villages and neighborhoods located in Kalecik district were interviewed face to face. A total of 40 producers, including 20 who have agricultural insurance and 20 who don’t, were surveyed using the full count method. The chi-square test and the nonparametric Spearman Correlation test were used in the statistical analysis performed using the SPSS 24 program. Agricultural insured producers were asked Likert-scale questions and their satisfaction with insurance services was measured. As a result of the chi-square test applied, a significant relationship was found between the status of agricultural insurance and total monthly income, total land size, total land area of Kalecik Karası grape, loss status over the past 5 years and the level of agricultural insurance knowledge. According to the results of the Spearman Correlation test, a significant relationship was found between the information questions about sales and marketing services, claims services, policy and additional coverage. Producers who don’t have agricultural insurance don’t want to have insurance because they find the premium amount to be high and their risks are low.
Keywords: Agriculture; Agricultural insurance; Spearman Correlation test; Chi-square test; Kalecik Karası grape